An Oncogenic Role for Alternative NF-κB Signaling in DLBCL Revealed upon Deregulated BCL6 Expression - Baochun Zhang; Dinis Pedro Calado; Zhe Wang; Sebastian Fröhler; Karl Köchert; Qian Yu; Sergei B. Koralov; Marc Schmidt‐Supprian; Yoshiteru Sasaki; Christine Unitt; Scott J. Rodig; Wei Chen; et al. (2015)
d Genetic loss of TRAF3 is associated with